Stellar populations of decoupled cores in E/S0 galaxies with sauron and oasis - McDermid, R; Emsellem, E; Shapiro, K; Bacon, R; Bureau, M; Cappellari, M; Davies, R; De Zeeuw, T; Falcón-Barroso, J; Krajnović, D; Kuntschner, H; Peletier, R; et al. (2006)
We summarize results from McDermid et al. (2006), who present a set of follow-up observations of the sauron representative survey of early-type galaxies. We used the oasis integral-field spectrograph (while at the Canada-France-Hawaii Telescope) to obtain high spatial resolution spectra of 28 elliptical and lenticular galaxies. These seeing-limited data have on average twice the spatial resolution of the sauron data, albeit over a smaller field. These new data reveal previously unresolved features in these objects' stellar kinematics, stellar populations, and ionized gas properties. In this contribution, we focus on the discovery of a population of compact kinematically decoupled cores in a number of our sample galaxies. These compact cores are related to regions of young stars, and counter-rotate around the host galaxy's minor axis. We compare these objects to previously known decoupled components, which in contrast are composed of old stars, and which rotate around axes unrelated to the host galaxy's kinematics or shape. A key difference between these two kinds of decoupled cores are their physical size and relative mass. The compact decoupled cores are smaller than a few hundred parsec, and constitute less than a few percent of the total galaxy mass. The classical decoupled cores exist on kiloparsec scales, and comprise around a factor 10 more mass. We suggest that the small components are only found with young ages because of their low mass-to-light ratio. We show that after a few Gyrs, these components fade into the background galaxy, making them more difficult to detect. We draw the following conclusions: 1) young stars found in early-type galaxies are very often associated with centrally-concentrated counter-rotating components; 2) the small mass fraction and kinematic decoupling of these cores suggests that the star formation is associated to minor accretion events, which effectively drive the spread in luminosity-weighted ages found in early-type galaxies; and 3) such decoupled components may be common in all early-type galaxies, but not directly observed due to their small contribution to the total galaxy light at older ages. © 2007 International Astronomical Union.